A critical assessment of the recent proposals and reports on the regulation of digital mergers. Issue 3 (October 2021) - Gürkaynak, Gönenç; Yeşilaltay, Kansu Aydoğan; Aydoğan, Zeynep Ayata
Abstract : This article examines the recent proposals and reports on the regulation of digital mergers in the European Union, United Kingdom, United States and other jurisdictions, with a particular focus on the proposals for presumptions against mergers. It argues that any intervention in digital mergers needs to calibrate a balance between preventing excessive levels of market concentration and promoting innovation and that any departure from existing laws should be justified. Against this background, this article concludes that the recent arguments for lowering the threshold for blocking digital mergers undermines the risk of chilling innovation and losing significant efficiencies, and does not rely on concrete evidence and sound economic theories.